Histopathological Observation on Experimental Aeromonas hydrophila Injection in Clarias batrachus ( Linn. ) - Supranee Chinabut; Pikul Jiravanichprisal (Agriculture and Natural Resources, 1990)
One hundred healthy walking catfish were experimentally injected intramuscularly with 0.1 ml. of normal saline ( 0.85 % NaCl ) containing 2.56 x 108 cells of Aeromonas hydrophila. Histopathological changes of skin, muscle, gills and internal organs were studied. Histopathological observations indicated that the gills and the internal organs appeared normal, whereas inflammatory responses of skeletal muscle of the early stage was detected. It was characterized by diapedesis of blood vessels in the hypodermal layer, hydropic degeneration of muscle fibres and myoseptum. Advanced stage was characterized by the appearance of dead cells of epidermis, dermis and hypodermis and formation of ulcerative lesions on the body surface. The natural healing process was observed and characterized by the migration of epithelial cells of epithelial cells to cover the lesion. In addition, fibrosis and granulation were observed by day 4. The lesion was completely healed within 3 weeks after the bacterial injection.